Flawed - Dorfman, Andrea (Richmond Hill, Ontario : Firefly Books, 2018)
"Flawed is an adaptation of the 2010 National Film Board of Canada production of the same name. Flawed traces the genesis of Andrea Dorfman's self-image - from the carefree days of her childhood to the gut-wrenching awkwardness of her adolescence, and beyond - as she navigates her romantic relationship with a plastic surgeon and her feelings surrounding her own self image her notion that cosmetic surgery makes people feel flawed."--
Adapted from the film Flawed.
Keywords: Dorfman, Andrea; Dorfman, Andrea -- Pictorial works; Self-acceptance.; Self-acceptance -- Pictorial works; Self-perception.; Self-perception -- Pictorial works; Body image; Body image -- Pictorial works; Surgery, Plastic -- Popular works; Surgery, Plastic -- Pictorial works